Framework for Consideration of Tool Selection in Bore Pile Work in Uncertain Field Conditions: Literature Study - Alexander Qurnain; Arief Saefudin; Rezi Berliana Yasinta (Jurnal Multidisiplin Sahombu, 2026)
The selection of bore pile drilling equipment is a technical decision influenced by multiple interrelated factors. In construction practice, subsurface conditions cannot be fully determined during the planning stage, while operational constraints and considerations of time, cost, and risk further shape the decision-making process. This paper presents a literature-based review aimed at developing a conceptual framework for selecting bore pile drilling equipment, with emphasis on subsurface uncertainty and its implications for construction execution. The study adopts a literature review approach by examining relevant scientific publications, standards, and regulations from the past ten years. The findings indicate that equipment selection should not be viewed as a single or absolute decision, but rather as a multidimensional and context-dependent evaluation process. The proposed framework is intended to support practitioners and researchers in understanding drilling equipment selection as part of risk management in bore pile foundation works